PENERAPAN GAMIFIKASI BERBANTUAN WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI PERSAMAAN LINEAR SATU VARIABEL KELAS VII SMP NEGERI 3 KABILA - Fatmawati Abas; Khardiyawan A.Y Pauweni; Taulia Damayanti (Universitas PGRI Sumatera Barat, 2026)
This study aimed to improve students’ mathematics learning outcomes on the topic of one-variable linear equations through the implementation of Wordwall-assisted gamification. The research was conducted in response to low student achievement, limited learning engagement, and the predominance of conventional teaching methods that had not optimally utilized interactive learning media. The study employed Classroom Action Research consisting of two cycles, each comprising planning, action, observation, and reflection stages. The participants were 26 seventh-grade students of SMP Negeri 3 Kabila in the 2025/2026 academic year. Data were collected through classroom observations and cognitive learning outcome tests administered at the end of each cycle. Observation data were used to assess teacher and student activities, while test results were analyzed based on the minimum mastery criterion of 72. The findings revealed a notable improvement in learning outcomes following the implementation of Wordwall-assisted gamification. Learning mastery increased from 70.94% in Cycle I to 86.92% in Cycle II. In addition, teacher activity improved from 69.04% to 92.85%, while student activity increased from 71.42% to 89.28%. Based on the results of the actions implemented, the application of Wordwall-assisted gamification can help improve students’ mathematics learning outcomes and active participation in learning one-variable linear equations.